THOUGHT STOPPING THERAPY EFFECTIVELY REDUCES THE LEVEL OF MENSTRUATION PAIN (DYSMENORRHORE) IN TEENAGE WOMEN - Hartati, Suryani; Laela, Sri (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2024)
Adolescent girls generally experience menstrual pain, or dysmenorrhea, which can interfere with their daily activities. This can be overcome by using thought-stopping therapy. The aim of this research is to find out whether thought-stopping therapy has an impact on menstrual pain (dysmenorrhea) in adolescent girls. This research was conducted through a quasi-experiment with a pre-test design and a post-test design with a control group. This research used a purposive sampling technique involving 48 respondents, conducted from January to April 2024 in the East Jakarta area. This study used a questionnaire about dysmenorrhea pain and the Numeric Pain Scale (NPS) pain scale. Respondents who experienced pain were undergoing thought-stopping therapy. The research results show that the majority of teenagers always experience moderate pain during menstruation, with a p-value of 0.831. After thought-stopping distraction therapy was carried out, there was a significant decrease in the level of pain from moderate to mild (p-value 0.735). Therapeutic nursing actions: stopping can reduce the level of pain in adolescent girls during menstruation . Distraction therapy: thought stopping is recommended to reduce dysmenorrhea pain in adolescent girls